Cardiac Surgery in Germany during 2014: A Report on Behalf of the German Society for Thoracic and Cardiovascular Surgery - Beckmann, Andreas; Funkat, Anne-Kathrin; Lewandowski, Jana; Frie, Michael; Ernst, Markus; Hekmat, Khosro; Schiller, Wolfgang; Gummert, Jan F.; Cremer, Joachim Thomas (The Thoracic and Cardiovascular Surgeon, 2015)
Based on a voluntary registry of the German Society for Thoracic and Cardiovascular Surgery (GSTCVS), data of all heart surgery procedures performed in 78 German cardiac surgical units during the year 2014 are presented. In 2014, a total of 100,398 cardiac surgical procedures (implantable cardioverter-defibrillator and pacemaker procedures excluded) were submitted to the registry. More than 14.2% of the patients were older than 80 years, describing an increase of 0.4% compared with the previous year. The unadjusted in-hospital mortality for 40,006 isolated coronary artery bypass grafting procedures (84.7% on-pump, 15.3% off-pump) was 2.6%. In 31,359 isolated valve procedures (including 9,194 catheter-based procedures), an in-hospital mortality of 4.4% was observed. This annual updated registry of the GSTCVS is published since 1989. It is an important tool for quality assurance and voluntary public reporting by illustrating current standards and actual developments for nearly all cardiac surgical procedures in Germany.
Keywords: cardiac surgery; outcome; registry; heart valve surgery; congenital heart disease; aortic surgery